Patrimonio alimentario y gastronómico de las parroquias rurales del cantón Latacunga. - Cando Molina, Pamela Yuliza (2022)
Given the evident devaluation of gastronomic traditions, this research aims to identify the food and gastronomic heritage of the rural parishes of Latacunga canton (Aláquez, Belisario Quevedo, Guaytacama, Joseguango Bajo, Mulaló, Once de Noviembre, Poaló, San Juan de Pastocalle, Tanicuchí, Toacaso) as a means of disseminating cultural diversity. From a qualitative approach, the inductive method was used to previously compile the historical, social and cultural data of the study area, through the bibliographic review of scientific articles, theses and development plan and land use planning (PDOT), where it has been determined that the combination and adaptation of the cultures from pre-Hispanic times to the present have given rise to activities such as agriculture and livestock that continue to this day, in addition, their knowledge and techniques of cultivation, as well as culinary and their main festivals highlighted by the Catholic faith and religion have become a legacy of identity. To carry out the inventory, the ethnographic method allowed the approach with the community in the field visits, through the interview and direct observation, relevant information is collected on the uses, customs, history and techniques, both for the cultivation of the main agricultural products of the area as of the representative gastronomic preparations. Based on the criteria of the “Food Heritage Atlas” manual (Importance for the community, ancestry), 10 agricultural products have been identified as food heritage: lupine, melloco, goose, mortiño, sambo, potatoes, corn , barley, broad beans, peas, which have been inventoried in tables made with the fields proposed by the "Atlas" and 10 dishes made as gastronomic heritage: Potatoes with guinea pig, Chicha de Jora, Sweet Sambo, Toasted, Caldo de Treinta y Uno, Humas with Coffe, Cooked, Chapo, Chaguarmishqui and Corn Tortillas, all stand out for being part of the daily or festive meal, which have been inventoried in the structure of the INPC files in the gastronomy sub-scope. Finally, the synthetic method was applied to summarize the results of the research in a proposal for an academic article, following the structure and model of the PASOS magazine, as a means of dissemination and contribution to the care and strengthening of cultural identity, for future generations.